Detecting facial expressions within a context of surprise and uncertainty - Gordillo León, Fernando; Mestas Hernández, Lilia; Fernández Núñez, Miguel; Pérez Nieto, Miguel Ángel; Arana Martínez, José M. (Anales de Psicología / Annals of Psychology, 2022)
Threatening expressions are detected quickly and accurately, warning the observer of the presence of a potential danger. During the detection process, a facial expression of surprise could play an important role as a cue for orientation in conditions of uncertainty that call for a swift and precise response. With a view to analysing this contingency, an experiment was conducted in which 70 subjects undertook a spatial cueing task that involved facial expressions of surprise (vs. neutral ones) as orientation cues, and facial expressions of fear, anger and happiness as target stimuli. The results revealed a priming effect of the expression of surprise solely in the detection of the expression of anger, reducing response times and the percentage of errors. The data indicate that the expression of surprise, when processed as an independent stimulus, could prime the detection of those stimuli that constitute a direct threat, such as the expression of anger, with this being a crucial distinction for understanding the circumstances in which the expression of anger is detected more effectively than other kinds of expressions.